ADHD, stress, and anxiety - Bob, Petr; Privara, Michal (Frontiers in Psychiatry, 2025)
Recent findings on stress and anxiety in attention deficit hyperactivity disorder (ADHD) suggest that specific processes related to brain developmental disorganization could create a vulnerable background that increases sensitivity to stress stimuli from the psychosocial environment. These basic neurodevelopmental processes are closely related to the developmental mechanisms of primitive functions and their integration or disintegration. In this context, the psychopathological processes that manifest in ADHD are linked to the mechanisms of disturbed inhibitory functions that may cause incongruent neural interactions (“neural interference”) between the more primitive functions and the higher levels of attentional and cognitive neural processes. These disturbed developmental processes may also determine increased sensitivity to stressful experiences that, in ADHD cases, could lead to the manifestations of various psychopathological symptoms such as disturbed attentional and motor functions, anxiety, and depression, among other cognitive and affective disturbances. These findings, based on previous research, suggest novel framework and hypothesis on how this neurodevelopment-based increased sensitivity to stress stimuli could manifest in the etiopathogenesis of ADHD in its relationship with cognitive, affective, and motor deficits.